PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 28 BUKIT KERIKIL KECAMATAN BUKIT BATU - Syaari Syaari; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Implementation of good teaching is inseparable from the plan or a good preparation. Therefore, in order to implement the necessary reinforcement learning social studies and preparation for the learning process can be more effective, efficient and focused. This research is motivated by the lack of IPS student learning outcomes, with an average grade of 65. Among the students of 20 people only 7 students who completed reached KKM with classical completeness 35%. This thesis presents the increase in the number of students who reached the KKM of 7 (35%) at the base score to 14 men (70%) in the first cycle and increased to 19 (95%) in the second cycle. This means that class into the sample has been completed in the classical style. An increase in the average learning outcomes of the basic score is 54.25 into 76.50 in the first cycle and 81.5 in the second cycle. An increase in teacher activity. At the first meeting of the first cycle of the percentage of activity the teachers are 58.33%, 70.83% the second meeting. While the second cycle of the first meeting with a percentage of 87.50%, and the second meeting increased 91.67%. While student activity also increased that the first meeting of the first cycle of the percentage of student activity is 54.17%, 66.67% the second meeting, the first meeting of the second cycle of 79.17% and a second meeting fixed with an average of 87.50%.Key words: Model Cooperative Learning Mind Mapping,Learning Outcomes IPS